Sistem Pakar Diagnosa Penyakit Glaukoma dengan Metode Certainty Factor Berbasis Website - Muhammad Satria; Muhammad Cordiaz (CV. Multi Kreasi Media, 2023)
Eyes are a very important sense tool for humans. Like other sense organs, the eye has a very important function, namely as a sense of sight. The eyes are very sensitive because the eyes are directly dealing with bacteria, infection or dust when we do activities. The hospital handles various complaints about diseases of the human eye, one of which is glaucoma. This is a problem for the Eye Hospital. For this reason, a research entitled